Varicella‐zoster virus infection in the pediatric population with acute lymphoblastic leukemia in Poland. Issue 12 (22nd May 2020) - Zawitkowska, Joanna; Lejman, Monika; Szmydki‐Baran, Anna; Zaucha‐Prażmo, Agnieszka; Czyżewski, Krzysztof; Dziedzic, Magdalena; Zalas‐Więcek, Patrycja; Gryniewicz–Kwiatkowska, Olga; Czajńska‐Deptuła, Aneta; Gietka, Agnieszka; Semczuk, Katarzyna; Hutnik, Łukasz; et al.
Abstract: Varicella‐zoster virus (VZV) infection in pediatric hemato‐oncology patients can be a therapeutic problem when children are exposed to immunosuppression. The aim of this study is to evaluate the incidence of VZV infection, antiviral therapy and outcome in children with ALL treated in polish hemato‐oncological centers between 2012 and 2019 years. This study included medical records of 1874 patients, aged 1 to 18 years, with newly diagnosed acute lymphoblastic leukemia. During chemotherapy, 406 children out of 1874 (21.6%) experienced viral infections. The incidence of VZV infection in the whole group children with ALL was 1.8%. Among them, 34 (8.4%) patients were diagnosed with VZV infection. Thirty‐five episodes of viral infections were identified. The median time of VCV therapy was 12 days. Herpes zoster infection occurred in 24 (70.6%) children, and varicella in 10 (29.4%) ones. The average time from the start of chemotherapy to the appearance of herpes zoster was 7.26 ± 4.05 months. VZV infection occurred mainly during the maintenance therapy, the reinduction and induction phases. There was no correlation between steroid dosage or type and subsequent zoster. The total lymphocyte count of these patients on the first day of zoster was reduced. No serious complications were observed due to this infection. All patients survived. In conclusion, a low incidence of VZV infection was observed among pediatric patients with ALL in Poland. This analysis indicates that currently used therapeutic methods are effective in children with cancer and VZV infection. The main focus should be on the prevention of delayed chemotherapy.